VA Video Connect for Clinical Care in Older Adults in a Rural State During the COVID-19 Pandemic: Cross-Sectional Study - Padala, Kalpana P; Wilson, Kerrie B; Gauss, C Heath; Stovall, Jessica D; Padala, Prasad R (JMIR Publications, 2020)
BackgroundThe COVID-19 pandemic has accelerated the need for telehealth at home. Although the Department of Veterans Affairs is a leading provider of telehealth, disparities may exist in reaching older veterans living in rural areas. VA Video Connect (VVC) is a video conferencing app that enables veterans to connect with their health care provider via a secure and private session. ObjectiveThe aim of this study was to examine the capability and willingness of older veterans to participate in a VVC visit during the COVID-19 pandemic. MethodsA cross-sectional study was conducted on older veterans (N=118) at the Central Arkansas Veterans Healthcare System. Participants were interviewed over the phone and responses to the following items were recorded: availability of internet, email, and an electronic device with a camera; veterans' willingness to complete an appointment via a VVC visit; and availability of assistance from a caregiver for those who were unable to participate in a VVC visit alone. ResultsParticipants' mean age was 72.6 (SD 8.3) years, 92% (n=108) were male, 69% (n=81) were Caucasian, 30% (n=35) were African Americans, and 36% (n=42) lived in a rural location. The majority reported having access to the internet (n=93, 77%) and email service (n=83, 70%), but only 56% (n=67) had a camera-equipped device. Overall, 53% (n=63) were willing and capable of participating in a VVC visit. The availability of internet access was significantly lower in rural compared to nonrural participants (P=.045) and in those with or less than a high school education compared to those who pursued higher education (P=.02). Willingness to participate in the VVC visit was significantly lower in rural compared to nonrural participants (P=.03). Of the participants who reported they were able and willing to partake in a VVC visit (n=54), 65% (n=35) opted for VVC and 35% (n=19) preferred a phone visit. In total, 77% (n=27) of the scheduled VVC visits were successful. ConclusionsDespite advances in technology, and willingness on the part of health care systems, there are some lingering issues with capability and willingness to participate in video telehealth visits, particularly among older adults residing in rural areas.